Performance Appraisal In Entrepreneurial University - Waney, G; Radianto, W.E.D. (Review of Management and Entrepreneurship, 2017)
Performance appraisal is one of the management control mechanisms that aim to ensure the behavior of the members of the organization led to the goals set earlier. This study aims to explore in depth how the professors interpret the performance appraisal applied in the entrepreneurial university. The qualitative research method with a single strategy case study was used in this study. Data collection methods were employed such as in-depth interviews, participant observation, and documentation. The performance appraisal was a tool to judge performance, support the strategy, control the faculty, improve the quality, and motivate the faculty. The study found the key to successful implementation of performance appraisal included the leadership commitment, participation of members of the organization, and dissemination that systematic and sustained.